Kuwait : Technical Assistance Report-Government Finance Statistics. (IMF Staff Country Reports; Country Report, 2018)
In response to a request from the Central Statistical Bureau (CSB) of Kuwait, a government finance statistics (GFS) technical assistance (TA) mission visited Kuwait City, Kuwait during April 29-May 3, 2018. This first GFS TA mission from the IMF's Statistics Department (STA) aimed to assist the CSB staff in compiling fiscal data according to the Government Finance Statistics Manual 2014 (GFSM 2014) and help them to issue this year's GFS bulletin according to the GFSM 2014 classification. In addition, the mission discussed with the Ministry of Finance (MoF) the possibility of resuming the reporting of the GFS data to the Fund for surveillance and dissemination in Government Finance Statistics Yearbook (GFSY).